Predictive indicators of the volumes of the secretions for the decanulation of patients in the intensive care unit (Research, Society and Development, 2021)
The aim of this study was to establish predictive indicators of secretion volumes for decannulation in intensive care unit patients. To measure the secretion, adhesive rulers were prepared for the vacuometers and standardization for suction with the measurement of 10ml of saline solution at 0.9% styrated during the suction process and another 10ml for cleaning of the suction system, totaling 20ml that were deducted from the totals collected during suction, such criteria were used in the same way in the entire sample. Of the 52 (59.77%) patients with secretion rate of 0 to 20ml, the appearance of the secretion was fluid, clear color and absence of secretion in the tracheostomy region. The phonoaudiological clinical parameters showed: adequate phonation and oral transit time and conditions to maintain the cuff deflated. Such results were significant for decannulation (p = 0.000). For 19 (21.84%) patients with secretion rate between 30 and 40ml, they presented the aspect of thick secretion, yellowish color and presence of secretion in the tracheostomy region. The phonoaudiological clinical parameters showed: dysphonic vocal quality, wet voice, slow oral transit time and difficulty in maintaining the cuff deflated. Such results were preponderant for non-decannulation with significance (p = 0.000) for all criteria.  The analysis of the volume of suctioned secretions, as well as their aspect and coloration, proved to be a significant indicator in the decannulation process, as it quantifies and offers measurable standards.